Pengaruh Pembiayaan Bagi Hasil dan Tingkat Kesehatan Bank Terhadap Kinerja Keuangan dengan Pembiayaan Bermasalah Sebagai Variabel Moderasi di Bank Umum Syariah di Indonesia Tahun 2021-2024 - Ihyani Syithrotul Ahammi; Farhadi Arifiansyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the effect of profit sharing finacing and bank health level on the financial performance of Islamic Commercial Banks in Indonesia, with Non Performing Financing (NPF) as a moderating variable. Using regression analysis on secondary data from 2021-2024, the findings reveal that the Financing to Deposito Ratio (FDR) has a significant positive effect on Return on Assets (ROA), while profit sharing financing, Capital Adequacy Ratio (CAR), BOPO, and NPF show no significant effect. Moreover, NPF does not moderate the relationship among variables, indicating that optimizing financing distribution remains essential for improving profitability. These results contribute to the literatur and provide pratical recommendations for bank management and regulators.